2022
DOI: 10.31234/osf.io/74jsd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-right handedness is associated with language and reading impairments

Abstract: Worldwide, the majority of people prefer using the right hand for most motor tasks. Because of the link between handedness and language hemispheric dominance, handedness has been studied for association with language-related disorders. No clear pattern has emerged from these studies, and inconsistencies have been attributed to small sample sizes, publication bias, and heterogeneous criteria for the definition of handedness and disorders.Here, we assessed the frequency of non-right handedness (NRH) in 10 distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Interestingly, the historical overview illustrates how attention on dyslexia benchmarks moves in spirals: new knowledge discharges old knowledge then to be restored and reused. Terms such as “visual”, “auditive”, and “phonological” and “laterality”, have been redefined across cultures and recirculated by new methods of assessment (see, e.g., Refs [ 63 , 64 , 65 , 66 , 67 , 68 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the historical overview illustrates how attention on dyslexia benchmarks moves in spirals: new knowledge discharges old knowledge then to be restored and reused. Terms such as “visual”, “auditive”, and “phonological” and “laterality”, have been redefined across cultures and recirculated by new methods of assessment (see, e.g., Refs [ 63 , 64 , 65 , 66 , 67 , 68 ]).…”
Section: Discussionmentioning
confidence: 99%
“…According to James and Engelhardt, handwriting may facilitate reading acquisition in young children [ 70 ]. A recent large metastudy concluded that there is an association between non-right handedness and reading and language impairments due to “shared biological pathways underlying brain lateralization, handedness, and cognitive functions” [ 63 ]. This points to research on keyboard writing using both hands and assessing if this has any long-term effect on language lateralization of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…asymmetry of a language area in the dyslexic brain, at least in boys and men. And, at least in boys, there is a deviation in the distribution of planum asymmetry, which, together with reports of an abnormal distribution of hand dominance in the dyslexic population (Abbondanza et al, 2022), make modeling asymmetry and laterality in animals potentially productive.…”
Section: Endophenotypes To Modelmentioning
confidence: 99%
“…There is a literature about non-right handedness ( Abbondanza et al, 2022 ) and right hemisphere activation ( Pugh et al, 2000 ) for language tasks in dyslexic populations that indicate an aberration in cerebral dominance. Also, a few studies have been published on the issue of structural planum temporale asymmetry as seen in in vivo imaging studies (for a review, see Shapleske et al, 1999 ).…”
Section: Endophenotypes To Modelmentioning
confidence: 99%
See 1 more Smart Citation